Indocyanine Green Retention Rate at 15 Minutes as a Key Predictor of Clinically Significant Portal Hypertension in Cirrhosis: Development and Validation of a Superior Non-Invasive Diagnostic Model - Hu, Han; Lai, Wei; Zhou, Tiantian; Zhu, Jie; Yan, Huadong (Turkish Journal of Gastroenterology, 2025)
Background/Aims: To assess the correlation between indocyanine green retention rate at 15 minutes (ICG-R15), liver stiffness mea surement (LSM), and other clinical indicators in cirrhotic patients, using hepatic venous pressure gradient (HVPG) as a reference and to evaluate the predictive capability of ICG-R15 for clinically significant portal hypertension (CSPH). Materials and Methods: From February 2023 to September 2024, 80 cirrhotic patients were recruited. Data collected included baseline information, laboratory results, HVPG measurements, and ICG-R15 via the ICG clearance test. Patients were classified into non-CSPH (n = 33) and CSPH (n = 47) groups based on HVPG. Pearson’s correlation analyzed relationships between HVPG, ICG-R15, LSM, and other indicators. Logistic regression was used to identify risk factors for CSPH and develop a predictive model, evaluated by receiver operating characteristic curve. Results: The CSPH patients showed lower white blood cell count, red blood cell count, hemoglobin, platelet count (PLT), and albumin, with higher total bilirubin (TBil), prothrombin time, LSM, and ICG-R15. Significant correlations were found between HVPG and ICG-R15 (r = 0.662) and LSM (r = 0.633) (both P < .001). The ICG-R15, LSM, PLT, and TBil were independent risk factors for CSPH. The model had an AUC of 0.947, sensitivity of 78.72%, and specificity of 96.97%. Conclusion: The ICG-R15 is a significant predictor of CSPH, and a model incorporating ICG-R15 can effectively assess disease severity and predict prognosis in cirrhotic patients. Cite this article as: Hu H, Lai W, Zhou T, Zhu J, Yan H. Indocyanine green retention rate at 15 minutes as a key predictor of clinically significant portal hypertension in cirrhosis: development and validation of a superior non-invasive diagnostic model. Turk J Gastroenterol. Published online October 10, 2025. doi:10.5152/tjg.2025.25155.